(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The paper purports to examine the latest developments of the judicial saga related to the “Lambert case” and, in particular, decision No. 647/2019 of the French Court of Cassation, through the lens of international human rights law. It focuses on two main aspects, which have proven to be critical elements in the case at stake: the difficult coordination between human rights treaty monitoring bodies’ diverging pronouncements and the nature and legal effects of a request for interim measures coming from human rights treaty monitoring bodies.